To solve the equation \( 13x + 26 = 3x - 34 \), follow these steps:
-
First, isolate the terms involving \( x \) on one side and constant terms on the other side. Subtract \( 3x \) from both sides:
\[ 13x - 3x + 26 = -34 \]
This simplifies to:
\[ 10x + 26 = -34 \]
-
Next, subtract 26 from both sides to isolate the \( x \) term:
\[ 10x = -34 - 26 \]
This simplifies to:
\[ 10x = -60 \]
-
Now, divide both sides by 10 to solve for \( x \):
\[ x = \frac{-60}{10} \]
This results in:
\[ x = -6 \]
Thus, the solution is \( x = -6 \).
The correct response is:
x=−6
x equals negative 6.